LOCAL KNOWLEDGE OF CIPATAT KOLOT ON THE CLIMATE ADAPTATION: SEED, ORGANIC FERTILIZER, AND HARVEST PROCESSING - Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Zuzy Anna; Rimun - Wibowo; Muhammad Shiddiq Ilham Noor (Patanjala: Journal of Historical and Cultural Research, 2021)
Climate change is characterized by several elements, namely unpredictable rainy and dry seasons, floods and unpredictable droughts. This study aims to determine the indigenous peoples’ local wisdom in adapting to climate change, which includes screening process of local paddy seeds, the use of organic fertilizers, and traditional harvest management strategies. The method used in this research is the qualitative research method combined with the ethnographic approach. This method is applied based on the consideration that the topic of this research is related to the culture and social of indigenous peoples. The data was collected by means of in-depth interviews, observation, and documentation. Informants were selected by using the purposive sampling technique. The results were scrutinized carefully by means of the triangulation process. The results of the study show the facts that the way indigenous peoples deal with climate change is by physically and physiologically selecting seeds and storing seeds for three months so that the seeds will grow stronger. In addition, they only selects paddies that has reached a full state of growth, that is mature to avoid going rotten even though the climate change occurs. Then, they have the traditional rice dryers to get rice dried, thereby enabling those to be more climate-resistant. They also use the organic fertilizer to reduce the production of emissions as a cause of global climate change. Perubahan iklim dapat diamati mulai dari musim penghujan dan musim kering yang tidak menentu, bencana banjir, dan kekeringan yang sulit untuk diprediksi. Penelitian ini bertujuan untuk mengetahui kearifan lokal pada masyarakat adat dalam beradaptasi terhadap perubahan iklim mulai dari seleksi benih padi lokal, penggunaan pupuk organik, dan manajemen panen secara tradisional. Metode yang digunakan adalah kualitatif dengan pendekatan etnografi. Metode ini diterapkan karena penelitian berkaitan dengan budaya dan sosial masyarakat adat. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi. Pemilihan informan menggunakan teknik purposive sampling. Kemudian, hasil pengumpulan data diteliti dengan cermat melalui triangulasi. Hasil penelitian menunjukkan bahwa masyarakat adat mengatasi perubahan iklim dengan melakukan seleksi benih secara fisik dan fisiologi dan menyimpan benih sampai dengan 3 bulan agar benih kuat dalam pertumbuhannya. Disamping itu, petani adat harus memanen padi matang sehingga padi tidak mengalami pembusukan meskipun terjadi perubahan iklim. Kemudian, masyarakat menggunakan mengelola hasil panen dengan alat pengering padi tradisional sehingga hasil panen padi lebih tahan iklim. Setelah itu, masyarakat adat menggunakan pupuk organik sebagai cara untuk memperkecil produksi emisi sebagai penyebab perubahan iklim secara global.